Letter from Ray D. Prueter to Jane Tolmach - Ray D. Prueter:::::: (1973)
A letter from Ray D. Prueter, the Mayor of Port Hueneme, to Jane Tolmach congratulating her on her election to the position of Mayor of Oxnard.